Penanganan Komplain dan Komunikasi Word-Of-Mouth (WOM) - Simanjuntak, Megawati; Hamimi, Ulfa Khairunnisa (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2019)
Submission of complaints by consumers is an important key in the issues of consumer empowerment. However, some consumers often do not want to complain because the process takes a long time and complicated. In fact, complaints from consumers need to be considered by producers to maintain their existence and improve the relations with consumers. Consumers who satisfied with their complaints handling are more likely to inform the product and producer to other customers. This study aims to determine the effect of complaints handling on Word-of-Mouth (WOM) communication. The design of this study using a quantitative and cross-sectional study with online survey methods conducted at the Bogor Agricultural University (IPB). Two hundred and eighthy five respondents were chosen by convenience sampling and met the requirement as passed the first level of undergraduate students of Bogor Agricultural University, and had complained that responsed by the marketers/producers. Data analysis used SEM method through Analysis of Moment Structures (AMOS) program. The result of the study shows that service recovery performance affected positively on perceived justice and satisfaction with complaints handling, otherwise satisfaction of complaints handling affected negatively on WOM behaviour. It means, the better the service recovery performance or the better complaints handling by marketer/producer, the better the perceived justice and satisfaction of complaints handling that felt by consumers. Furthermore, the more satisfied with complaints handling, the more communication will be made by consumers to other individuals or groups by WOM.